Kemampuan Mengidentifikasi Nilai-Nilai Kehidupan Dalam Cerpen Melalui Penerapan Model Pembelajaran Project Based Learning (PJBL) Di Kelas XI SMA Negeri 1 Labuapi - Nurmalayani, Ayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This study generally describes the ability of class XI students of SMA Negeri 1 Labuapi in identifying life values. This picture is taken from the results of the best practices of learning activities using project based learning methods. This research concludes several things. First, the activeness of students in learning is very high because most learning activities are responded to by all or most students. Second, almost all students have very good and good attitude or character. There were not even students who had bad behavior and only a few of them behaved well enough. For honesty, 87% of students (20 people) are very good and 13% (3 people) are good. For discipline 57% (13 people) are very good, 26% (6 people) are good, and 17% (4 people) are good enough. For responsibility attitude 83% (19 people) are very good, 8.5% (2 people) are good, and 8.5% (2 people) are good enough. Meanwhile, for socialist attitudes 52% (12 people) are very good, 39% (9 people) are good, and 8.5% (2 people) are good enough. Third, learning short stories by using Project Based Learning (PjBL) learning models assisted by local or contextual teaching materials, can improve students' abilities in identifying life values in short stories, which is up to 83%. In this case, 19 out of 23 students completed / reached the KKM. Meanwhile, some things that can be recommended as a follow-up to the results of this activity are (1) teachers are advised to use the Project Based Learning (PjBL) learning model because it can increase student activity; and (2) teachers are advised to use material that is contextual or close to students' daily lives because it will be more quickly understood.